Intermedia agenda-setting from the far right? Three case studies on spillover effects by alternative media in Germany - Tilman Klawier (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2023)
Right-wing alternative media can increase their public impact if they succeed to set their issues on the mainstream media's agenda. In three qualitative case studies, the present article explores whether and how such intermedia agenda-setting occurs in Germany. Special attention is given to spillover effects between different actors, both at the level of attention and tone towards the issues. Furthermore, the analysis of news articles is supplemented with Twitter data to account for the role of social media. Two of the case studies indicate that right-wing alternative media contributed to push pseudo-scandals into the mainstream. The analyses also reveal alternative news outlets with particular agenda-setting power and point to the crucial role of tabloid media as a bridge to the mainstream. The third study, however, which centered on the Global Compact for Migration, presents a case where intermedia agenda-setting failed. Against this background, the article discusses the conditions under which intermedia agenda-setting by right-wing alternative media is likely to occur and how journalists should deal with such attempts
urn:nbn:de:bsz:100-opus-22202
Keywords: 330; alternative media; intermedia agenda-setting; far right; scandals; Twitter; Germany